Head and neck osteosarcomas: Analysis of treatment trends and survival outcomes in the United States (2004–2016). Issue 11 (17th July 2021) - Shim, Timothy; Chillakuru, Yeshwant; Darwish, Christina; Chalif, Eric; Strum, David; Benito, Daniel A.; Mulcahy, Collin F.; Monfared, Ashkan
Abstract: Background: Head and neck osteosarcoma (HNOS) is a rare primary bone tumor with limited data to guide treatment approaches. Methods: The NCDB was used to identify patients diagnosed with HNOS. Kaplan–Meier and Cox multivariate regression were used to examine the impact of each treatment on overall survival (OS). Results: We identified 821 patients diagnosed with HNOS. Utilization of neoadjuvant chemotherapy + surgery increased from zero cases in 2004 to 24% of cases in 2016. Among surgically treated patients, 5‐year OS was 55.8% (CI: 51.7–60.1%). No difference was seen in OS between each treatment cohort on multivariate analysis. However, neoadjuvant chemotherapy + surgery + adjuvant chemotherapy had improved 18‐month survival compared to surgery alone (95.8% vs. 78.5%, p = 0.031). Conclusions: Our study demonstrated no survival benefit in perioperative chemotherapy or radiation therapy; however, short‐term survival improvement in patients receiving both neoadjuvant and adjuvant chemotherapy displays promise and requires further investigation.